Effect of microstructure and texture on the impact transition behaviour of thermo-mechanically treated reinforcement steel bars. (15th January 2016) - Sk., Md. Basiruddin; Khan, A.K.; Lenka, S.; Syed, B.; Chakraborty, J.; Chakrabarti, D.; Deb, Arghya; Chandra, S.; Kundu, S.
Abstract: In order to develop earthquake resistant or blast resistant structures for freezing environmental condition, it is necessary to evaluate the impact toughness and impact transition behaviour of thermo-mechanically treated (TMT) reinforcement steel bars. Considering the difficulty in preparing standard geometry Charpy V-notch specimens from the TMT rebar, a new specimen design, on semi-circular cross-section, is proposed in the present study for the impact testing of rebars. Tensile testing and impact toughness testing have been carried out on the TMT rebar samples of different diameters (10–16 mm) to study the processing-microstructure-mechanical property relationship. Among the investigated rebars, higher section rebar (16 mm) showed the best combination of strength, ductility and impact toughness possibly due to the higher tempered martensite rim fraction and the presence of degenerated pearlite and lower bainite at the core region of that rebar. Large fraction of high-angle boundaries and the presence of gamma-fibre texture could have contributed to the lowest ductile–brittle transition temperature (DBTT) in 12 mm rebar. Impact toughness can also be influenced by the residual stress distribution inside the rebars. Graphical abstract: Highlights: Evaluation of impact properties of thermo-mechanically treated reinforcement bars. Use of a new specimen design for Charpy impact testing of reinforcement bars. Microstructure, texture, residual stress, impact toughness correlation in rebars. High rim-fraction and degenerated pearlite at core improve strength and toughness. Gamma-fibre texture and compressive residual stress are also beneficial for toughness.